2012
DOI: 10.1111/jmi.12003
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature‐SEM study of dihedral angles in the ice‐I/sulfuric acid partially molten system

Abstract: SummaryThe transport and mechanical properties of partially molten materials are influenced by the wetting behaviour of the melt with respect to the crystalline solid. The equilibrium microstructure of an ice + melt system was examined using low-temperature scanning electron microscopy. The samples were prepared by spraying a liquid solution of H 2 O-H 2 SO 4 into liquid nitrogen and packing the frozen particulates into aluminium capsules. Samples were then sintered at -35• C or -55• C (above the eutectic temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 39 publications
3
35
1
Order By: Relevance
“…In contrast, the dynamics of freezing forces the solutes to segregate and form the veins of freeze-concentrated solutions engulfed by the ice (Blackford, 2007;Cheng et al, 2010;McCarthy et al, 2013;Bogdan et al, 2014;Krausko et al, 2014). The solutes in the freeze-concentrated solution, here probably in the surface layer only, experience not only an increased concentration (Heger et al, 2005;Kania et al, 2014;Krausko et al, 2015a) but also a changed pH (Heger et al, 2006;Krausková et al, 2016;Papadimitriou et al, 2016;Rérolle et al, 2016) and polarity (Heger and Klan, 2007).…”
Section: Ffs At a High Temperature: Brine Fingers Formationmentioning
confidence: 99%
“…In contrast, the dynamics of freezing forces the solutes to segregate and form the veins of freeze-concentrated solutions engulfed by the ice (Blackford, 2007;Cheng et al, 2010;McCarthy et al, 2013;Bogdan et al, 2014;Krausko et al, 2014). The solutes in the freeze-concentrated solution, here probably in the surface layer only, experience not only an increased concentration (Heger et al, 2005;Kania et al, 2014;Krausko et al, 2015a) but also a changed pH (Heger et al, 2006;Krausková et al, 2016;Papadimitriou et al, 2016;Rérolle et al, 2016) and polarity (Heger and Klan, 2007).…”
Section: Ffs At a High Temperature: Brine Fingers Formationmentioning
confidence: 99%
“…Subsequently, Fukazawa et al () showed via Raman spectroscopy the presence of SO42 peaks (981 cm −1 ) at triple junctions in ice cores collected from Antarctica. In other more recent work from C. McCarthy et al (), high‐resolution low‐temperature scanning electron microscopy was used to study the effects of 4.67 wt % H 2 SO 4 doping on the interfacial energies between sintered ice grains at −35°C. In the study, it was found that an equilibrium solid‐melt microstructure of ice and aqueous H 2 SO 4 forms after sintering and that the solid‐liquid equilibrium dihedral angle was found to be approximately 30°.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, it was found that an equilibrium solid‐melt microstructure of ice and aqueous H 2 SO 4 forms after sintering and that the solid‐liquid equilibrium dihedral angle was found to be approximately 30°. As given in equation , the position of the melt with respect to the grains is given by a force balance of the interfacial energies, where γ ss and γ SL are the interfacial energies of the solid‐solid interface and solid‐liquid interface, respectively, and θ is the solid‐liquid dihedral angle subtended at the at the corner of a fluid filled pore (C. McCarthy et al, ; Nye & Frank, ). cos()θ2=γss2γSL …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations